Disaster Resilient Village in Padang City: How Padang City Efforts to Define the Disaster - Sari Nurul Fadhilah; Roni Ekha Putera; Desna Aromatica; Edi Hasyimi (Sawala : Jurnal Administrasi Negara, 2022)
Disaster Resilient Village is a program to reduce disaster risk by involving the community. Padang City has the highest potential and highest population is at stake in West Sumatra. Padang City has won the 2021 Adhiwirasana Toughness Award. Due to budget constraints, Padang been in a vacuum of program implementation from 2016 to 2020. Even sub-districts implemented only received a low rating. The community is motivated to implement the program because they are willing to use private funds. This is interesting because there is a gap in the form supported by achievements from the government and community motivation, but it's still low in program implementation. The research question is how is the management of the disaster resilient urban village program by the Padang City Regional Disaster Management Agency? This study uses qualitative method and management function theory, this research focuses on how actors to plan, organize, motivate, and control the program. The study results of the study indicate that the management of the disaster resilient urban village program in Padang City has not implemented optimally due to budget constraints, implementation that is not in accordance with general guidelines and the low assessment obtained by sub-district that have implemented the program.